Changing patterns of American ascendancy. Top graduate programmes in economics: Historical evolution and recent evidence - John O'Hagan (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2020)
The focus of this paper is on a very specific aspect of the 'internationally-organized machine' of economics, namely the evolution and location of the top PhD programmes which underlie the profession. The first part of the paper provides an overview narrative of the historical evolution of PhD programmes in economics from 1880, drawing on existing literature. The changing roles of Europe and the US is the primary focus in this regard, given that together they still dominate the top 50 rankings of the top economics departments in the world. The second part of the paper is empirical, and novel in terms of the data constructed. It attempts to bring the narrative up to the present time by looking at the cohorts of winners of the main young economist awards in economics in the US and Europe over the last twenty years or so and to chart at which universities they obtained their undergraduate degrees and doctorates
Keywords: 330; economists; PhD; history; American Economic Association; European Economic Association